Access of Clean Water and Sanitation with The Incidence of Environmental-Based Diseases in The Working Area of The Oesapa Sub-District - Debora G. Suluh; Ragu Theodolfi; Agustina; Ferry WF Waangsir (Jurnal Penelitian Pendidikan IPA, 2023)
Sanitation is an effort to prevent disease that focuses on environmental health efforts for human life. The purpose of this study was to determine access to clean water and the condition of basic sanitation facilities in the Oesapa Village, Kupang City. Sources of clean water used by the people of Oesapa Sub District consist of 72% dug wells, 15% PDAM, and 12% tank water. Ownership of clean sir facilities: 78% use privately owned SAB and 22% use neighbor-owned (shared use). The condition of clean water facilities with a high-risk level of 53%, moderate 32%, high 13% and very high 2%. Condition of family latrines 38% high-risk level, 61% low-risk level. SPAL conditions have a low-risk level of 91%, a medium of 5% and a high 4%. There is a relationship between the condition of clean water facilities and the incidence of environmental diseases in the Oesapa sub-district and there is no relationship between the condition of the sanitation facilities (latrines and SPAL) and the incidence of environmental-based diseases in the Oesapa sub-district.